2005
DOI: 10.1093/ageing/afi044
|View full text |Cite
|
Sign up to set email alerts
|

Morale in the oldest old: the Umeå 85+ study

Abstract: a large proportion of the oldest old had high morale. The most important factors for high morale were the absence of depressive symptoms, living in ordinary housing, having previously had a stroke and yet still living in ordinary housing, not feeling lonely and low number of symptoms. The PGCMS seems applicable in the evaluation of morale among the oldest old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
3
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 31 publications
3
50
3
10
Order By: Relevance
“…Life satisfaction among the elderly has become a critical issue in geriatric care [5,6]. Evaluating life satisfaction predictors with ''nest status'' as an independent variable, the regression analysis demonstrated that ''nest status'' was very important in predicting life satisfaction among the elderly, and that ''empty-nest status'' was negatively related with life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life satisfaction among the elderly has become a critical issue in geriatric care [5,6]. Evaluating life satisfaction predictors with ''nest status'' as an independent variable, the regression analysis demonstrated that ''nest status'' was very important in predicting life satisfaction among the elderly, and that ''empty-nest status'' was negatively related with life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective quality of life can be defined in terms of life satisfaction (LS), subjective well-being, and happiness, etc. [5,6]. Life satisfaction is believed to be an evaluation of life in general [6].…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of psychological well-being is morale, which among elderly populations is linked to a decreased risk of depression, increased optimism, and other aspects of psychological health (Leung et al, 2005;von Heideken Wagert et al, 2005;Woo et al, 2005;Giltay et al, 2006). A longitudinal study found that reduced morale and increased depression in the elderly are predictors of increased risk of injury due to falls (Anstey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The growing evidence for a steady increase of the number of centenarians worldwide was paralleled by several community-based longitudinal and cross-sectional studies aiming to determine possible psychobiological particularities of these individuals [5][6][7][8][9][10]. These studies showed that the known predictors of mortality such as socio-demographic factors, smoking and obesity are less important in this age group.…”
Section: Introductionmentioning
confidence: 99%